2007
DOI: 10.1093/jaoac/90.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Analgesic Components of Spasmomigraine® Tablet by Liquid Chromatography with Ultraviolet Detection

Abstract: A procedure was developed for the determination of the analgesic components of Spasmomigraine® tablets, which are ergotamine (I), propyphenazone (II), caffeine (III), camylofin (IV), and mecloxamine (V). They were subjected to high-performance liquid chromatography on a column (300 × 3.9 mm, 10 μm particle size) packed with μ-Bondapak C18. Separations were achieved with the mobile phase methanol–water–triethylamine (60 + 40 + 0.1, v/v/v) flowing at a rate of 1.5 mL/min, and quantitative determination was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For body tissues LC-MS methods are generally required to achieve the low detection limits necessary. With LC-UV ergotamine can be detected with other active ingredients using a C18 column with a mobile phase of methanol-water-triethylamine (60 + 40 + 0.1, v / v / v ) and detection at 254 nm [ 93 ].…”
Section: Specific Applicationsmentioning
confidence: 99%
“…For body tissues LC-MS methods are generally required to achieve the low detection limits necessary. With LC-UV ergotamine can be detected with other active ingredients using a C18 column with a mobile phase of methanol-water-triethylamine (60 + 40 + 0.1, v / v / v ) and detection at 254 nm [ 93 ].…”
Section: Specific Applicationsmentioning
confidence: 99%
“…Camylofin dihydrochloride (CMF) is an antimuscarinic drug which is used as an antispasmodic drug. Chemically, it is known as a 3-methylbutyl 2-(2-diethyl-aminoethylamino)-2-phenyl-acetate hydrochloride [1,2]. Diclofenac potassium (DCF) is a nonsteroidal anti-inflammatory drug (NSAID).…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey revealed that there is no method for the simultaneous determination of these compounds. There are other publications for determination of these compounds but in combination with other components by other analytical techniques like HPLC, spectrophotometry and colorimetric [4][5][6][7][8][9][10][11][12][13][14][15][16].There is a GC method reported for the analysis of Camylofin dihydrochloride [17]. There are, however, no publications for simultaneous determination of these drugs in such pharmaceutical preparation.…”
Section: Introductionmentioning
confidence: 99%